Differences in predictive factors for post-traumatic stress disorder encompassing partial PTSD and full PTSD: a cross-sectional study among individuals exposed to the November 13, 2015 Paris attacks - Berthail, Benoit; Trousselard, Marion; Lecouvey, Gregory; Le Roy, Barbara; Fraisse, Florence; Peschanski, Denis; Eustache, Francis; Gagnepain, Pierre; Dayan, Jacques (Frontiers in Psychiatry, 2024)
Background When faced with a surge of physically injured individuals, especially following a traumatic event like an attack, frontline practitioners prioritize early triage. Detecting potential psychological injuries soon after such events remains challenging. Some individuals might develop post-traumatic stress disorder (PTSD) according to DSM-V criteria. Others may exhibit PTSD symptoms without meeting full diagnostic criteria, termed partial or sub-syndromal PTSD, a less-explored area in literature. This study aims to identify predictive factors for both full and partial PTSD. Method In a cohort of victims of the 2015 Paris attacks, multinomial logistic regressions explored predictive factors for partial or full PTSD status 8 to 18 months post-attacks. Analyses considered pre, peri, and posttraumatic factors chosen from literature review and univariate analysis within each group. Results Within the cohort, 50 individuals showed no signs of PTSD, 35 experienced partial PTSD, and 30 presented with full PTSD. After logistic regression, risk factors associated with full PTSD included a history of trauma (OR = 1.30, CI [1.02-1.66], p < 0.05), the intensity of peri-traumatic physical reactions (OR = 1.22, CI [1.09-1.36], p < 0.001), the difficulties in suppressing intrusive thoughts (OR = 1.11, CI [1.02-1.21], p < 0.013). Only the intensity of peri-traumatic physical reactions emerged as a risk factor for partial PTSD (OR = 1.13, [CI 1.02-1.24], p < 0.001). Discussion This study revealed that a history of trauma, the intensity of peri-traumatic physical reactions (e.g., tachycardia, trembling, flushes, numbness.), and the difficulties in suppressing intrusive thoughts constitute risk factors for the development of full PTSD. Moreover, the study identified that only the intensity of peri-traumatic physical reactions emerged as a risk factor for partial PTSD. These findings seem to underscore the significance of peri-traumatic experiences in influencing the development of post-traumatic stress symptoms. Conclusion This study emphasizes the significance of examining peri-traumatic reactions in PTSD development, suggesting its potential as a straightforward screening tool for post-traumatic stress disorder. It also underscores the influence of prior traumatic experiences, before de novo traumatization, in shaping vulnerability to PTSD and illuminates the crucial role of compromised control of intrusive thoughts that could perpetuate PTSD.